Insider Ownership and Investment Efficiency - Bibek Bhatta (Queen's University Belfast, Queen's Management School, 2020)
Agency problems in firms are known to influence suboptimal capital investment decisions. Using panel data of publicly listed firms in India, we find evidence that increased insider ownership is associated with lower investment efficiency, i.e. as insider ownership increases, firms show tendency to make capital investments beyond the optimal level. However, we do not find evidence of increased insider ownership leading to underinvestment (below the optimal level of capital investment). A plausible explanation, consistent with theory, is that such insiders are making capital investments for private gain and empire-building rather than in the best interest of the firm. Additional analyses show that the presence of independent directors on the board of firms mitigates such value-destroying investments stemming from increased insider ownership.
Keywords: G31; G32; G34; 330; Investment efficiency; Tobin's Q; insider ownership; suboptimal investment; overinvestment